Nonlinear analysis of rotating machinery running on foil-air bearing - Hassan, Mohd Firdaus
This research is about study effect of curvature for modeling the bump foil structure in the simultaneous solution of foil-air bearing (FAB) rotor dynamic problems. Most recent research in foil-air bearing (FAB) rotor dynamic analysis has been limited to a simple bump foil model in which the individual bumps were modeled as independent spring-damper (ISD) subsystems. In these studies, the dynamics of the corrugated bump foil structure are studied using the finite element (FE) technique and simultaneous technique to calculate the result of the data. A full foil structure modal model (FFSMM) is created and then adapted into the rotordynamic FAB problem solution scheme, instead of the ISD model. A modal model is being limited into five modes. The rotor-bearing model is also validated against experimental and theoretical results in the literature. From this study, it showed there is no effect of curvature for modeling the bump foil structure. This is because the final result identical with the non-curvature or linear modeling the bump foil structure. Furthermore, the transient trajectory of the journal is identical with the linear form.